Genetic testing in the evaluation of individuals with clinical diagnosis of atypical Sturge–Weber syndrome. Issue 4 (29th January 2023) - Yeom, SangEun; Cohen, Bernard; Weiss, Clifford R.; Montano, Carolina; Wohler, Elizabeth; Sobreira, Nara; Hammill, Adrienne M.; Comi, Anne
Abstract: Sturge–Weber Syndrome (SWS) is a rare vascular malformation disorder characterized by abnormal blood vessels in the brain, skin, and eye. SWS is most commonly caused by a somatic mosaic GNAQ‐p. Arg183Gln variant. In this series, 12 patients presented for clinical evaluation of SWS but were noted to have atypical features, and therefore germline and/or somatic genetic testing was performed. Atypical features included extensive capillary malformation on the body as well as the face, frontal bossing, macrocephaly, telangiectasia, overgrowth of extremities, absence of neurologic signs and symptoms, and family history of vascular malformations. Five patients had a somatic GNAQ or GNA11 pathogenic variant, one patient had a somatic mosaic likely‐pathogenic variant in PIK3CA, and another one had a somatic mosaic deletion that disrupted PTPRD . The other five patients had germline variants in RASA1, EPHB4, or KIT . Our findings suggest that patients presenting for SWS evaluation who have atypical clinical characteristics may have pathogenic germline or somatic variants in genes other than GNAQ or GNA11 . Broad germline and somatic genetic testing in these patients with atypical findings may have implications for medical care, prognosis, and trial eligibility.